2021
DOI: 10.7717/peerj.12352
|View full text |Cite
|
Sign up to set email alerts
|

Global gap-analysis of amphipod barcode library

Abstract: In the age of global climate change and biodiversity loss there is an urgent need to provide effective and robust tools for diversity monitoring. One of the promising techniques for species identification is the use of DNA barcoding, that in Metazoa utilizes the so called ‘gold-standard’ gene of cytochrome c oxidase (COI). However, the success of this method relies on the existence of trustworthy barcode libraries of the species. The Barcode of Life Data System (BOLD) aims to provide barcodes for all existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
(131 reference statements)
2
3
0
Order By: Relevance
“…In accordance with our observations, there are several other studies pointing out considerable gaps in the reference libraries for different taxa [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, there are not many gap-analysis studies focusing on phytoplankton taxa.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our observations, there are several other studies pointing out considerable gaps in the reference libraries for different taxa [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, there are not many gap-analysis studies focusing on phytoplankton taxa.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that 91% of described species lack associated sequence data sourced from type specimens. A similar problem has been found for marine animals, including amphipod crustaceans, where only about 10% of accepted species have genetic barcodes (Jażdżewska et al 2021, Mugnai et al 2021.…”
Section: Impact Of Molecular Techniquessupporting
confidence: 57%
“…This bias can be particularly striking in certain geographical regions where potential prey are poorly known and broadly misrepresented in those databases, which is the case of intertidal invertebrates in West Africa (e.g. Porter & Hajibabaei 2018, Jażdżewska et al 2021. In our study, we tried to reduce such bias by sampling prey from the study area, therefore allowing higher match rates with dietary samples.…”
Section: Comparison Of the Performance Of Molecular (Coi And 16s Prim...mentioning
confidence: 99%